Pattern of Antimicrobial Susceptibility for Salmonella Typhi in Dhaka Medical College Hospital from 2013-2014 (Journal of Dhaka Medical College, 2017)
Multidrug resistant Salmonella spp has been emerged as a cause of concern. This study was done to evaluate recent status in antimicrobial susceptibility pattern of Salmonella typhi isolated from blood in Dhaka Medical college Hospital.Methods- The retrospective study was done over a two year period between January 2013 to December 2014 at Microbiology laboratory, Dhaka Medical College. A total of 203 isolates of Salmonella typhi obtained from blood cultures. Both the indoor and outdoor patients were enrolled in this study.Results- During the two year study period, total 203 cases were enrolled. Among them 66% were male with a male to female ratio 2:1. The bulk (55%) cases were in the age group of 15-30 years, 34% cases were in less than 15 years and 10% cases were between the ages of 31-45 years. Regarding antibiotic sensitivity pattern, 90.14% strains were sensitive to amikacin, 90.47% to gentamycin and amoxyclav. 89.16% to doxycycline, 83.75% to cotrimoxazole, 71.42% to azithromycin and 86.2% to ceftazidime. All the Salmonella were sensitive to ceftriaxone, 95.07% were sensitive to ciprofloxacin and 88% were nalidixic acid resistant Salmonella typhi (NARST).Conclusion- Ceftriaxone may be used to treat typhoid fever cases and quinolone has no longer efficacy to treat such cases. Azithromycin may be used as an alternative drug if it is found susceptible in culture and sensitivity testing.J Dhaka Medical College, Vol. 25, No.2, October, 2016, Page 115-118